2013
DOI: 10.5414/cncs107951
|View full text |Cite
|
Sign up to set email alerts
|

An intra-abdominal abscess or "rind" as a consequence of peritoneal dialysis-associated pseudomonas peritonitis

Abstract: Background: Abdominal CT imaging has defined characteristics of two pathological entities specific to peritoneal dialysis patients. Both are associated with serious peritoneal complications. One is comprised of ascites accompanied by septation and loculated fluid pockets as a complication of bacterial peritonitis. The other is the syndrome of encapsulating peritoneal sclerosis. We present the evolution of a single, thick-walled fluid collection as a consequence of relapsing Pseudomonas aeruginosa peritonitis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Studies have shown that peritoneal dialysis can be successfully resumed in patients after early catheter removal (1). Development of an intra-abdominal abscess is a rare complication of peritonitis and has been seldom reported in the literature (4,5). Abscess formation specifically after catheter removal is uncommon and has been reported in small case reports (4,5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that peritoneal dialysis can be successfully resumed in patients after early catheter removal (1). Development of an intra-abdominal abscess is a rare complication of peritonitis and has been seldom reported in the literature (4,5). Abscess formation specifically after catheter removal is uncommon and has been reported in small case reports (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…Development of an intra-abdominal abscess is a rare complication of peritonitis and has been seldom reported in the literature (4,5). Abscess formation specifically after catheter removal is uncommon and has been reported in small case reports (4,5). Clinical findings of persistent fever, abdominal pain, and tenderness along with leukocytosis are suggestive of abscess development and necessitate further radiographic investigation.…”
Section: Discussionmentioning
confidence: 99%